Reducing direct physical disturbance also mitigates hidden drivers of decline in a threatened seagrass meadow - Griffin, Kingsley J.; Johnston, Emma L.; Poore, Alistair G. B.; Vergés, Adriana; Clark, Graeme F. (Frontiers in Conservation Science, 2024)
Physical disturbances typically cause ecological impacts within areas of direct contact (primary disturbances) but can also impact surrounding areas through other mechanisms (secondary disturbances). Secondary disturbances are often overlooked, especially in marine ecosystems where sufficiently detailed observation can be difficult to obtain. For example, boat moorings create circular clearings in seagrass meadows by physically scouring the seabed, but visible impacts extend beyond this into surrounding areas due to disturbances such as increased sediment transport, edge effects, and shading from boats. Previous studies on impacts of moorings have not distinguished between primary and secondary disturbances, and secondary disturbances are rarely accounted for in environmental management. We used spatial modelling to examine the primary and secondary disturbances associated with moorings in a meadow of the threatened seagrass Posidonia australis. We compared the disturbance from traditional ‘swing’ moorings with ‘environmentally friendly’ moorings (EFM) designed to reduce scour. Within the scour zone (0-5 m from moorings), we compared seagrass cover around swing moorings with cover around EFM. Further from moorings (5-25 m), we tested the degree of association between seagrass cover and secondary disturbances that may accumulate with mooring density and be influenced by mooring design. We found that mooring design affected the degree of direct disturbance, with cover of P. australis in the scour zone of standard moorings ~49% lower than that of EFMs (p < 0.01). Mooring density had cumulative negative effects on P. australis cover in the surrounding meadow, but the influence of mooring density was reduced when most moorings were EFMs. This suggests that secondary effects contingent on direct physical disturbance (e.g. sediment transport, fragmentation, edge effects) may be stronger than the general influence of moored boats (shading). We use the findings to simulate two broad policy scenarios for mooring designs in P. australis meadows: installing only EFM, or only traditional moorings. The simulations suggest that using only EFM would lead to a 14.2% increase (~164 m2), whereas installing only traditional moorings would lead to a 16% (~187 m2) loss of P. australis cover in this already highly disturbed meadow. Synthesis and applications: We demonstrate a nondestructive approach to assessing primary and secondary disturbances driving the distribution of a threatened seagrass and simulate a range of potential management scenarios that could assist in conserving the species.